Physiologic variants, benign processes, and artifacts from 106 canine and feline fdg‐pet/computed tomography scans - Randall, Elissa; Loeber, Samantha; Kraft, Susan (Veterinary radiology & ultrasound, 2014)
18F‐Fluoro‐deoxyglucose positron emission computed tomography (FDG‐PET/CT) is an emerging diagnostic imaging modality in veterinary medicine; however, little published information is available on physiologic variants, benign processes, and artifacts. The purpose of this retrospective study was to describe the number of occurrences of non‐neoplastic disease‐related FDG‐PET/CT lesions in a group of dogs and cats. Archived FDG‐PET/CT scans were retrieved and interpreted based on a consensus opinion of two board‐certified veterinary radiologists. Non‐neoplastic disease‐related lesions were categorized as physiologic variant, benign activity, or equipment/technology related artifact. If the exact cause of hypermetabolic areas could not be determined, lesions were put into an indeterminate category. A total of 106 canine and feline FDG‐PET/CT scans were included in the study. In 104 of the 106 scans, a total of 718 occurrences of physiologic variant, areas of incidental benign activity, and artifacts were identified. Twenty‐two of 23 feline scans and 82 of 83 canine scans had at least one artifact. Previously unreported areas of increased radiopharmaceutical uptake included foci associated with the canine gall bladder, linear uptake along the canine mandible, and focal uptake in the gastrointestinal tract. Benign activity was often seen and related to healing, inflammation, and indwelling implants. Artifacts were most often related to injection or misregistration. Further experience in recognizing the common veterinary FDG physiologic variation, incidental radiopharmaceutical uptake, and artifacts is important to avoid misinterpretation and false‐positive diagnoses.